The influence of open innovation on domestic sales in Brazilian industry: an analysis of the Innovation Survey 2014 based on structural equation modeling - Fábio Hiroshi Tomoyose; Isabel Cristina dos Santos; Ana Cristina de Faria (BBR: Brazilian Business Review)
This research analyzes the influence of open innovation strategy on the participation of innovations in the context of domestic sales in the Brazilian industrial sector. To perform this analysis, available data were extracted from the PINTEC 2014 Innovation Survey. In applying structural equation modeling (SEM), we found that open innovation has a direct and positive influence on the sales of new products and services in the domestic market, albeit with a modest effect. The same analysis was applied to the relationship between open innovation and domestic sales, which was found to be mediated by the impacts caused by innovation. In other words, open innovation influences the participation of innovations in domestic sales, both directly and indirectly. Besides verifying the relationship among the concepts presented in this study, it was possible to estimate their effects and make a realistic contribution to the debate, emphasizing that innovation, despite being an essential condition, is not sufficient to generate strong impacts on domestic sales, according to PINTEC 2014 respondents. To achieve high impacts, it is necessary to continuously promote and support innovation for the generation of growth.